Pengaruh Permainan Tradisional Ular Naga Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Mahdia, Nabila; Rusmayadi, Rusmayadi; Kurnia, Rika; Rusliana, Faradillah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Social-emotional development in early childhood is a crucial foundation for shaping children's character and interpersonal skills in the future. However, learning activities that lack collaborative social interaction often hinder this development. This study aims to examine the effect of the traditional game Ular Naga (Dragon Snake) on the social-emotional development of children aged 5–6 years at TK Insan Masagena. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group model. The sample consisted of 16 children selected through purposive sampling, with 8 children in the experimental group and 8 in the control group. Data were collected through observation, testing, and documentation. Data analysis was conducted using descriptive statistics and the non-parametric Wilcoxon Signed Rank Test. The results showed an Asymp. Sig (2-tailed) value of 0.012 < 0.05, indicating a significant difference before and after treatment in the experimental group. Thus, the Ular Naga game has a positive and significant impact on children's social-emotional development. These findings imply that incorporating traditional games into early childhood education can be an effective strategy for enhancing children’s social and emotional skills in an engaging and natural way. The main contribution of this study lies in strengthening the literature on integrating local cultural elements into holistic and contextual learning approaches in early childhood education, while also promoting the revitalization of traditional games as developmental tools